Effect of Credit Risk on the Performance of Nepalese Commercial Banks - Bhattarai, Yuga Raj (NRB Economic Review, 2016)
This study has examined the effect of credit risk on performance of Nepalese commercial banks. The descriptive and causal comparative research designs have been adopted for the study. The pooled data of 14 commercial banks for the period 2010 to 2015 have been analyzed using regression model. The regression results revealed that ’non-performing loan ratio’ has negative effect on bank performance whereas ’cost per loan assets’ has positive effect on bank performance. In addition to credit risk indicators, bank size has positive effect on bank performance. Capital adequacy ratio and cash reserve are not considered as the influencing variables on bank performance. This study concludes that there is significant relationship between bank performance and credit risk indicators.